1988
DOI: 10.1143/jjap.27.983
|View full text |Cite
|
Sign up to set email alerts
|

Raman Spectral Behavior of In1-xGaxP (0<x<1)

Abstract: We report on a Raman study of In1-x Ga x P over the whole range of alloy compositions, x. The additional peak, which appeared for x\lesssim0.98 and about which various interpretations have been proposed, is found to be constructed by two unresolved modes. The Raman spectra indicate that this alloy system has a modified two-mode behavior. The spectral half width of a TO mode broadened in the middle of the alloy composition. This is partly due to the stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…In addition, it is believed that there is a TOphonon peak between the two LO-phonon peaks. 11,12 In early Raman studies on the effects of ordering, no major change in the Raman spectrum was observed. With recent improvement in the sample qualities, however, there have been several reports 7-10 of major effects of ordering on the ͑001͒ Raman spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is believed that there is a TOphonon peak between the two LO-phonon peaks. 11,12 In early Raman studies on the effects of ordering, no major change in the Raman spectrum was observed. With recent improvement in the sample qualities, however, there have been several reports 7-10 of major effects of ordering on the ͑001͒ Raman spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…Now we turn to the GaP:In impurity mode. Kato et al [9] observed a quasi-degenerate TO-LO mode at ~390 cm -1 in the In-dilute limit of (Ga,In)P, which they assigned as the GaP:In impurity mode. Since then the question of the location of the GaP:In mode was not re-examined.…”
Section: (Ga In)asmentioning
confidence: 99%
“…at ~347 cm -1 [8], the GaP:In mode was identified within the GaP TO-LO band, i.e. at ~390 cm -1 [9]. This is taken as responsible for strong overlapping of the Ga-P and In-P bands in the alloy, resulting in a complicated phonon behavior [10].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] For ternary alloys a distinction was made so far between the two extreme where infrared-active phonon mode frequencies vary as a function of the alloy composition: A single band of transverse ͑TO͒ and longitudinal ͑LO͒ phonon modes, which shift continuously between those of the binary constituents, and which is commonly termed as ''one-mode'' behavior. Accordingly, for the ''twomode'' behavior, two infrared active phonon bands occur close to the frequencies of the binary constituents.…”
Section: Introductionmentioning
confidence: 99%